THE IMPORTANCE OF DESIGNING AN EFFICIENT CITY TRANSPORT INFRASTRUCTURE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Transport infrastructure is the main element of any city. It allows people, goods and services to travel from one place to another. Our cities cannot function without efficient transportation systems and infrastructure. However, transportation is a major cause of greenhouse gas emissions and air pollution. With such a central role, it is vital that the transport infrastructure is in good condition and efficient for the future.